PEMBUATAN DAN UJI MUTU SEDIAAN MASKER GEL PEEL-OFF DARI SARI BUAH PEPAYA CALIFORNIA (Carica papaya L.) - taufiq, taufiq (Akademi Farmasi Yamasi Makassar, 2023)
Research has been carried out on the manufacture and quality test of the peel off gel mask preparation from papaya juice (Carica papaya L.) Moringa leaves were taken from the home garden area on Jl. Bontoduri 6 N0.14 C, then made papaya juice, after the juice was produced. fruit. Then made a mask base, then added papaya juice. And carried out ornanoleptic testing, pH, dry time, and homogeneity. The results showed that the pH with a concentration of 15% = 6.14 Concentration of 20% = 6.24. Testing Dry time where the concentration of 15% = 20 minutes and 20% = 24 minutes. Organoleptic testing of simplicia is thick, orange in color, has no odor. And testing the homogeneity of both concentrations is homogeneous